HOLLAND'S THEORY APPROACH IN CAREER GUIDANCE SERVICES IN SCHOOLS - Auladina Lathifa; A. Muri Yusuf; Afdal (Yayasan Citra Dharma Cindekia, 2021)
Career Guidance is an effort to encourage individuals to be able to know and master, get to know the world of work, and improve experiences in accordance with the form of life they expect. One of the theories that can be used to identify the world of work that is suitable for individuals is Holland's Theory, which sees individual personality as a benchmark in career choice and adjustment to the work environment. Therefore, the author aims to examine more deeply about Holland's Theory in career guidance services in schools to find out more in depth through various available and relevant sources. This study uses a literature review method because the method used in this study is supported by relevant theories and sources. The results of this study indicate that a person can make good career decisions when his personality type is accepted in the work environment